An Inventory and Assessment of Sample Sources for Survey Research with Agricultural Producers in the U.S. Issue 7 (3rd July 2022) - Ulrich-Schad, Jessica D.; Li, Shuang; Arbuckle, J. G.; Avemegah, Edem; Brasier, Kathryn J.; Burnham, Morey; Kumar Chaudhary, Anil; Eaton, Weston M.; Gu, Wei; Haigh, Tonya; Jackson-Smith, Douglas; Metcalf, Alexander L.; et al.
Abstract: Researchers need probability samples to collect representative survey data about the behaviors and attitudes of agricultural producers they study in relation to the natural resources that they manage, yet obtaining accurate and complete sampling frames is challenging. We extract data from a publication database to identify the most commonly used sampling frame sources in survey research of agricultural producers in the U.S., finding that government program participant lists are used most often, while private vendor samples are increasingly being purchased. Based on our research experience, we find that for many projects, private vendors can provide the most rigorous samples. Given that survey methods remain a useful and popular method for studying the behaviors and attitudes of producers on a variety of topics, such an assessment and guide is needed for researchers and practitioners.